The knowledge of undergraduate nursing students in the city of Baixada Fluminense in performing oral hygiene of intubated patients (Research, Society and Development, 2022)
The study aimed to analyze the knowledge of nursing students from a Higher Education Institution in the Baixada Fluminense of oral hygiene in highly complex intubated patients. Methodology: This is a field research, with a qualitative approach, approved by the CEP of the Municipal Health Secretariat of Rio de Janeiro, by CAAE: 65400817.8.0000.5279, Opinion Number: 1.965.932, whose scenario took place in a Higher Education Institution Private from Baixada Fluminense, with 30 nursing students as participants, who were submitted to an open questionnaire, and the speeches were transcribed and interpreted by the content analysis method, in the thematic modality, which generated a thematic unit and two categories. Conclusion: The students pointed out that oral hygiene is essential for patients admitted to the ICU, to serve as a measuring instrument to reduce the risk of infections, as a consequence, reduce stress and suffering.